Effect of kinematics on ground reaction force during single-leg jump landing in children: a causal decomposition approach in jumpers and non-jumpers - Cruz-Montecinos, Carlos; Estevan, Isaac; Skypala, Jiri; Tapia-Malebrán, Claudio; García-Massó, Xavier (PeerJ, 2024)
BACKGROUND: The interaction between joint kinematics and kinetics is usually assessed by linear correlation analysis, which does not imply causality. Understanding the causal links between these variables may help develop landing interventions to improve technique and create joint-specific strengthening programs to reduce reaction forces and injury risk. OBJECTIVE: Therefore, the aim of this study was to analyze the causal interaction between lower limb sagittal kinematics and vertical ground reaction force (VGRF) during single-leg jump landing in children who are jumpers (volleyball and gymnastics) and non-jumpers, using the causal empirical decomposition method. Our hypothesis is that children who participate in jumping sports, compared to those who do not, employ a different joint strategy to regulate ground reaction forces during landing, particularly at the ankle level. METHODS: Two groups were compared: the jumpers group (n = 14) and the non-jumpers (control group, n = 11). The causal interaction between sagittal kinematics and VGRF was assessed using ensemble empirical mode decomposition (EEMD) and time series instantaneous phase dependence in bi-directional causality. The relative causal strength (RCS) between the time series was quantified as the relative ratio of absolute cause strength between kinematics and VGRF. RESULTS: A significant interaction between joint and group was found for RCS (p = 0.035, η 2 p = 0.14). The post-hoc analysis showed the jumpers group had higher ankle-to-VGRF RCS than the control group (p = 0.017, d = 1.03), while in the control group the hip-to-VGRF RCS was higher than the ankle-to-VGRF RCS (p = 0.004, d = 0.91). CONCLUSION: Based on the causal decomposition approach, our results indicate that practicing jumping sports increases the causal effect of ankle kinematics on ground reaction forces in children. While non-jumper children rely more on the hip to modulate reaction forces, jumper children differ from non-jumpers by their greater use of the ankle joint. These findings could be used to develop specific training programs to improve landing techniques according to practice level, potentially helping to reduce the risk of injury in both athletes and non-athletes.
Keywords: biomechanika; hlezenní kloub; lidé; Volleyball; Ankle Joint; Female; dítě; Lower Extremity; Motor competence; Humans; volejbal; Non-linear relationship; mužské pohlaví; gymnastika; Biomechanical Phenomena; dolní končetina; ženské pohlaví; Motor control; Gymnastics; Male; Child; Jumping sports